EXPLORING 35-44 YEAR OLD MEN’S HEALTH BEHAVIOUR: A QUALITATIVE PERSPECTIVE - Silkane, Vineta; Austers, Ivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Upon reaching 35-44 year of age, men experience their first health problems, often because of an unhealthy way of life e.g., smoking, physical inactivity, unhealthy nutrition habits, etc. In comparison with other age groups, these men rarely look for medical help, thus, opening themselves up to a number of potentially negative consequences e.g. health risks in future. This study explores the health behaviour of 35-44 year old men by conducting semi-structured in-depth interviews with 48 participants. The data are further analysed using inductive thematic analysis. Results indicate the presence of three main types of men’s behaviour: 1) participants with positive attitude towards one’s health and practice of health behaviour, 2) well-informed participants with intentions to perform health behaviour as well as excuses not to follow these intentions, 3) men with negative attitude towards one’s health and lack of practice of health behaviour.